Development and characterization of Katchamita mango (Mangifera indica L.) fruit leather. - Castelo, Jenny Ann Talaman
The study focused on the development and characterization of Katchamita mango fruit leather. Four methods of preparing fruit leather with varying pre-treatment and drying conditions: F1 (hot break method dried at 60°C for 10 hours), F2 (hot break method dried at 80°C for 6 hours), F3 (cold break method dried at 60°C for 10 hours), and F4 (cold break method dried at 80°C for 6 hours) were subjected to Rank Test for Preference to determine the most preferred Katchamita mango fruit leather. Kruskal-Wallis test at 5% level of significance showed that Katchamita mango fruit leather dried at 60°C for 10 hours (F1 and F3) was the most preferred. F1 was considered as the most preferred method because hot break method of pretreatment for fruit leather production retains more of natural fruit flavors and preserves color. The most preferred Katchamita mango fruit leather was characterized using proximate analyses, physicochemical analyses, and sensory evaluation. The product had 12.34% moisture content, 0.49% crude protein content, 0.45% crude fat content, 0.51% crude fiber content, 0.51% to 0.95% ash content, and carbohydrate content ranging from 85.26% to 85.70%, all in dry basis. Katchamita mango fruit leather had a water activity value of 0.64, total soluble solids content of 38.80°Brix, pH ranging from 4.04 to 4.36, and TA of 0.72% citric acid. The product was evaluated as having moderately tough texture, a very minimal intensity of sourness, a moderate level of sweetness, a dark yellow color, an adequately perceptible mango flavor, and a moderately perceptible mango odor. The general acceptability of Katchamita mango fruit leather was great when subjected to consumer testing involving fifty (50) young adults with the age bracket of 18-35 years old and fifty-one (51) children with the age bracket of 8-17 years old which could mean that the product has a high potential for commercialization.